Die Ost-Erweiterung der Europäischen Informationsgesellschaft:: Technologische Anpassung als Modus politischer Institutionalisierung - Schaper-Rinkel, Petra (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The EU has adopted a common sei of technological standards and an organizational framework in the field of telecommunication, which have the applicant states to accept. Seemingly a pure question of technology outside the political process, this set actually contributes to a hierarchical division of labour between old and new members of the EU. Furthermore the benchmarking process, in which the progress of the applicant states is measured, forces the applicant states in competition for best adaption and provides westem companies with optimal information for their investment decisions.